Pelayanan Administrasi Kependudukan Pembuatan AktaKelahiran di Dinas Kependudukan Dan Pencatatan SipilKabupaten Banyumas (Studi Terhadap Pelaksanaan PeraturanDaerah Nomor 18 Tahun 2015 Tentang AdministrasiKependudukan Di Kabupaten Banyumas) - Endah Nur Ratri; Wahyu Hariadi; Agoes Djatmiko; Haris Kusumawardana (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
This study aims to find out how the implementation of population administrationservices for making birth certificates at the Department of Population and CivilRegistration of Banyumas Regency and to find out how the obstacles or obstaclesfaced and the efforts made by the Office of Population and Civil Registration ofBanyumas Regency, it can be concluded that the implementation of servicespopulation administration making birth certificates at the Department ofPopulation and Civil Registration of Banyumas Regency in accordance withRegional Regulation Number 18 of 2015 concerning Population Administrationin Banyumas Regency where the service has fulfilled the quality of service well allaspects in the service are based on applicable regulations and have standardprocedures in carrying out properly according to applicable regulations.However, the implementation of the service has not been optimal, there are stillobstacles in its implementation, there are several obstacles and problems thatmust be improved, such as the ability of employees to update the system andHuman Resources for the Department of Population and Civil Registration ofBanyumas Regency.